EFFECT WORKLOAD ON WORK STRESS TO DISTRICT ATTORNEY EMPLOYEE IN SAMARINDA - Damayanti, Desita Dyah; Fadilla, Tasya; Alamanda, Karina Putri; MSEPS2, Panitia (Jurnal Ekonomi dan Manajemen, 2022)
A workload is a number of activities carried out or the time given to complete work that is perceived by individuals as excess work activities, working hours, work pressure, and individual satisfaction levels. The many demands of work in the work environment make work stress appear. This study aims to see the effect between workload and work stress on employees of the Samarinda City Public Prosecutor's Office. The number of research samples in this study was 46 respondents. In data collection, the workload scale used consisted of 12 items with a Cronbach alpha of 0.850 and the work stress scale consisted of 13 items with a Cronbach alpha of 0.835. The results of this study indicate that workload has a significant and positive effect on work stress on employees of the Samarinda City Public Prosecutor's Office with a correlation coefficient of workload on work stress of 0.507 with p = 0.000 (p <0.05).